Resilience and mental health among perinatal women: a systematic review - Hajure, Mohammedamin; Alemu, Solomon Seyife; Abdu, Zakir; Tesfaye, Gebremeskel Mulatu; Workneh, Yadeta Alemayehu; Dule, Aman; Adem Hussen, Mustefa; Wedajo, Lema Fikadu; Gezimu, Wubishet (Frontiers in Psychiatry, 2024)
Objective This review aimed to assess the current evidence on the relationship between resilience and mental health employed in response to the impacts of mental health. Method This review was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA). The protocol of this review was registered on the International Prospective Register of Systematic Reviews (PROSPERO: CRD42023470966). Three authors searched peer-reviewed articles using several electronic databases, including Scopus, PubMed/MEDLINE, Psych Info, EMBASE, and Web of Science, from September to October 2023 and included all the studies from any time until November 1, 2023. The review included all eligible quantitative observational and qualitative studies, irrespective of geographical boundaries. Result Depression, anxiety, and post-traumatic stress disorders were found to be the most common, but not the only, mental health disorders during the perinatal period, and higher maternal resilience during perinatal periods was found to reduce mental health disorders. It was also found that pregnant women were more resilient to mental health disorders than postpartum women. Tolerance of uncertainty and a positive cognitive appraisal, women’s self-behavior and family functioning, and protective psychosocial resources such as dispositional optimism, parental sense of mastery, self-esteem, gratitude, and forgiveness were found to be the most common mechanisms of resilience among perinatal women. Older age, having an adolescent partner, family income, and distress were found to affect resilience. Conclusion Noting that women’s resilience is an important tool to prevent perinatal mental health disorders, maternal healthcare providers need to counsel perinatal women on resilience-boosting mechanisms, such as applying self-behavior and having social support or close family relationships. It is recommended to counsel or provide psychosocial interventions for the woman’s companion or partner to give strong support for the woman in each of the perinatal periods. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=470966, identifier CRD42023470966.